Modification and Structure Evaluation of Clorogenic Acid Compounds as BACE1 Inhibitors for the Treatment of Alzheimer - Ardy Tanfil. T; Tunas Alam (LPPM Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
Alzheimer's disease remains an unresolved health issue to this day, mainly due to the limitations and adverse effects of available medications. Alzheimer's is characterized by the accumulation of amyloid plaques formed through the action of the BACE1 enzyme. Chlorogenic acid has shown potential as an Alzheimer's drug candidate due to its diverse neurological benefits. The aim of this research is to develop chlorogenic acid as a BACE1 inhibitor by modifying its molecular structure to enhance its effectiveness. The study employs in silico methods, involving structural modifications of chlorogenic acid and assessing its activity using molecular docking. The research employs in silico approaches to modify the structure of chlorogenic acid and analyze the interactions of the resulting compounds with BACE1 through molecular docking. The modified compounds demonstrate improved potential as BACE1 inhibitors as they can directly bind to the amino acid residues ASP A:32 and ASP A:228 on BACE1. Chlorogenic acid's structure can be modified to yield novel compounds with the potential to inhibit BACE1, offering a promising solution for Alzheimer's treatment. This study provides valuable insights for the development of more effective and safer Alzheimer's drugs.